Entrepreneurship & Attention Deficit/Hyperactivity Disorder: A Large-Scale Study Involving the Clinical Condition of ADHD - Dan Lerner; Ingrid Verheul; Roy Thurik (Institute of Labor Economics (IZA), 2017)
A growing conversation has emerged linking ostensibly dark or pathological individual-level characteristics to entrepreneurship. Attention Deficit/Hyperactivity Disorder (ADHD) emerged as a proof-of-concept phenomenon. Recent studies in entrepreneurship journals have made great strides – articulating the theoretical relevance of ADHD-type behavior in entrepreneurship, and suggesting a positive link consistent with narratives in the popular press. While the recent research has made important inroads, quantitative studies have yet to empirically examine ADHD in line with its theoretical roots and definition – as a full-blown clinical disorder. The present paper contributes by providing a theoretically-empirically aligned test of the connection between clinical ADHD and entrepreneurial intention as well as action.
Keywords: L26; I12; 330; nascent venturing; ADHD; attention deficit/hyperactivity disorder; entrepreneurial intentions; entrepreneurial action